The effects of bank mergers on small business lending in Germany - Thomas Bloch (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2008)
In this paper, we examine the impact of mergers among German savings banks on the extent to which these savings banks engage in small business lending. The ongoing consolidation in the banking industry has sparked concerns about the continuous availability of credit to small businesses which has been further fueled by empirical studies that partly confirm a reduction in small business lending in the aftermath of mergers. However, using a proprietary data set of German savings banks we find strong evidence that in Germany merging savings banks do not significantly change the extent to which they lend to small businesses compared to prior to the merger or compared to the contemporaneous lending by non-merging banks. We investigate the merger related effects on small business lending in Germany from a bank-level perspective. Furthermore, we estimate small business lending and its continuous adjustment process simultaneously using recent General Method of Moments (GMM) techniques for panel data as proposed by Arellano and Bond (1991).
Keywords: G21; G28; G34; C23; 330; Bank mergers; small business lending; Sparkasse; Übernahme; Fusion; Kreditgeschäft; Firmenkundengeschäft; Klein- und Mittelunternehmen; Kredit; Deutschland